Rash in lapatinib-treated patients is not associated with human leukocyte antigen polymorphisms. (July 2015) - Parham, Laura R; Briley, Linda P; King, Karen S; Byrne, Julie; Rappold, Erica; Goss, Paul E; Spraggs, Colin F
Rash is a common side effect of lapatinib treatment. Since human leukocyte antigen ( HLA ) alleles have been implicated in multiple drug-induced cutaneous reactions, this study investigated the association of HLA alleles with lapatinib-induced rash. 1191 participants from a large lapatinib monotherapy trial underwent HLA genotyping, and allele carriage frequencies between rash cases and controls were compared. This analysis had adequate power to detect an association of common HLA alleles with rash, similar to those reported previously. No HLA alleles were significantly associated with lapatinib-induced rash, including the previously identified lapatinib hepatotoxicity biomarker HLA-DRB1 *07:01 (p = 0.87). The present study is consistent with the view that lapatinib-induced rash is not the consequence of HLA-restricted, immune-mediated mechanisms.